Degradação de hormônio sintético por meio de lacases fúngicas imobilizadas em fibras de Luffa cylindrica - Lacerda, Monike Fabiane Alves Ribeiro (2015)
The 17α-ethinylestradiol (EE2) is a synthetic estrogen used in contraceptive and hormone replacement therapies; is an environmental contaminant potential, it is not completely removed in sewage treatment plants, reaching the aquatic environment, with the aggravating factor interfere the endocrine system of humans and other animals. For this reason there is great interest in the removal of EE2 present in wastewater, surface water and groundwater. Thus the use of laccase for this purpose may be promising because of low specificity of this enzyme to the substrate. Therefore, the aim of this study was to evaluate the effectiveness of laccase produced by the fungus Pleurotus ostreatus immobilized in Luffa cylindrica (loofah) fibers in EE2 degradation. Therefore the best means for production of laccase and the best conditions of pH and temperature were investigated. The immobilization process was realized and removal of the EE2 assay was conducted in flasks and in a batch reactor. Thus, the best means for producing laccase were Potato Dextrose and Potato Dextrose Modified with guariroba straw. Readings taken with 2.2-Azino-bis (3-ethylbenzothializone-6-sulfonic acid) - ABTS revealed best pH between 3.6 and 4.6 and optimal band temperature between 30 and 50 °C for free and immobilized enzymes. The laccase produced in both media had an apparent molecular mass of 40 kDa. The best conditions found for the immobilization process were glutaraldehyde concentration of 2% and reaction with the support 1 hour under stirring (120 rpm); drying the loofah prior to the reaction with glutaraldehyde; time of 24 hours of immobilization. The immobilized enzyme showed best enzymatic activity in alkaline pH, and at higher temperatures, compared to the free enzyme. The operational stability, storage and thermostability were not significant. Best removals for tests in flasks were 79.22% and 75.0% for free and immobilized enzyme, respectively. As the tests carried out in the reactor showed removal by adsorption of 99.3% and 73.14% in the Luffa cylindrica, the immobilized enzyme. However, it is necessary to optimize the immobilization process, as well as the test in the reactor to increase the degradation EE2.